Prevalence of noninfectious respiratory disease in thoroughbred racehorses - Jusoh, Siti Zurida; Fateh Mohamed, Bashir Ahmad; Omar, Mohamed Ariff; King Murdoch, Alistair Ivon (2011)
The objective of the study was to identify the most common noninfectious respiratory diseases in Thoroughbred racehorses and to determine effect on their performance. One hundred and thirty randomly selected records of Thoroughbred racehorses at the Perak Turf Club, Ipoh, Perak, Malaysia diagnosed with noninfectious respiratory disease and with complains of poor athletic performance accompanied by coughing, exercise intolerance and abnormal respiratory noises were obtained. Among the data recorded and analyzed were surgery and racing performance records, which were used to determine the most prevalent noninfectious respiratory diseases in the Thoroughbred racehorses. The results showed that the most common noninfectious respiratory disease in Thoroughbred racehorses is exercise-induced pulmonary haemorrhage (EIPH) 49.2%), recurrent laryngeal neuropathy (28.2%), respiratory allergy (10%), epiglottic entrapment (EE) (7.7%), displacement of the soft palate (DDSP) (3.8%) and subepiglottic cysts (0.8%). The study also showed that surgical correction for recurrent laryngeal neuropathy (RLN) (Grade IV and Grade V), epiglottic entrapment, dorsal displacement of soft palate (Persistent) and subepiglottic cysts (SEC) gave good resolution and good prognosis for recovery. Thus surgical treatments of Thoroughbred racehorses with noninfectious respiratory disease can improve their athletic performance.